Financial policy, 1939-45 - Sayers, R. S. (London : H. M. Stationery Off., 1956)
This book, the eighteenth of the Civil Histories published by the British on the Second World War, deals with the role of finance. It is based largely on official papers, but it has been written from a viewpoint entirely outside the Civil Service. It is alleged that Mr. Churchill, when inviting Sir Kingsley Wood to be his Chancellor of the Exchequer, told him that he did not wish to hear the word Treasury until the end of the War. The book sometimes supposed that the sole duty of finance in time of war is to keep out of the way. it describes the action taken by the Government, and explains why at the time the policy seemed sufficient. In no country during the War did the Government succeed in organising the whole operating life to the same extent as we did in the United Kingdom, and the importance of Professor Sayers' book is that he describes in some detail how this was done financially.
Includes index.
sju 22/01/2019
Loans
Keywords: Finance, Public; World War, 1939-1945; United Kingdom